Urban informal sector - Surjit Singh (New Delhi, 1994)
For a variety of reasons, urban poor, especially those involved in unorganized activities, have not received as much attention of the policy makers and researchers as their counterparts in the rural areas. The framework of the study provides for in depth look at such activities/enterprises in the manufacturing sector of a growing Indian metropolis-Jaipur. More specifically, it probes the socio economic profile of the entrepreneurs in the informal manufacturing enterprises; analyzes the input-output linkages of the enterprises including procuring of raw materials and marketing of produce; analyzes the institutional and technological linkages with formal enterprises in respect of acquisition of skills, procurement of capital stock, hiring practices, credit requirements and other functional links; understands the employment and income generation potential of these enterprises; and the problems faced by them. The understanding provided by this study of some of the vital issues would go a long in strengthening these tiny sector enterprises in several ways, such as ensuring delivery of inputs in an appropriate way, making arrangements for the marketing of the products in an efficient manner and above all, designing supportive infrastructure of credit, information and skill formation. Contours of such policies and programmes are logically deduced and are clearly spelt out in the study.
Keywords: Urbanization